2022
DOI: 10.1172/jci.insight.152559
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell immunoreceptor drives atopic dermatitis by modulating oxidized CaMKII-involved mast cell activation

Abstract: Allergens have been identified as potential triggers in patients with atopic dermatitis (AD). Patients with AD are highly sensitive to cockroach allergen. The underlying mechanism, however, remains undetermined. Here, we established a cockroach allergen–induced AD-like mouse model, and we demonstrate that repeated exposure to cockroach allergen led to aggravated mouse skin inflammation, characterized by increased type 2 immunity, type 2 innate lymphoid cells (ILC2s), and mast cells. Increased mast cells were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 92 publications
0
11
0
Order By: Relevance
“…Mast cell activation leads to degranulation, vasodilation, plasma extravasation, and recruitment of immune cells [ 27 , 28 ]. Mast cell activation is involved in the pathogenesis of pain and many chronic inflammatory diseases, including atopic dermatitis [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mast cell activation leads to degranulation, vasodilation, plasma extravasation, and recruitment of immune cells [ 27 , 28 ]. Mast cell activation is involved in the pathogenesis of pain and many chronic inflammatory diseases, including atopic dermatitis [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MCs are required in allergen-induced skin inflammation. DC immunoreceptor (DCIR) is upregulated in skin MCs of patients with atopic dermatitis and mediates allergen binding and uptake ( 7 ). Thus, MCs have a strategic position in host defense, the response to allergens, and immune homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…RNA sequencing study confirmed increase of DC markers CD80 and CD86, as well as markers typical of atopic DCs (OX40L+, FCϵR1+) in both lesional and nonlesional skin of keloid patients ( 85 ). Unlike in atopic dermatitis, where DCs have been linked to mast cell activation and Th2, Th17 and Th22 differentiation ( 134 , 135 ), the exact action of DCs in keloids is less clear.…”
Section: The Roles Of Immune Cells In Keloid Formationmentioning
confidence: 99%